The ways social networks shape reflection on early significant clinical experiences in medical school - Stasiuk, Samantha; Hubinette, Maria; Nimmon, Laura (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Background: Medical curricula are increasingly providing opportunities to guide reflection for medical students.  However, educational approaches are often limited to formalized classroom initiatives where reflection is prescriptive and measurable. There is paucity of literature that explores the personal ways students may experience authentic reflection outside of curricular time.  The purpose of this study was to understand how social networks might shape dimensions of reflection. Methods: This study employed a qualitative social network analysis approach with a core sample of seven first year undergraduate medical students who described their relationships with 61 individuals in their networks. Data consisted of participant generated sociograms and individual semi-structured interviews.Results: Many learners struggled to find significant ways to involve their social networks outside of medicine in their new educational experiences.  It appeared that some medical students began in-grouping, becoming more socially exclusive.  Interestingly, participants emphasized how curricular opportunities such as reflective portfolio sessions were useful for capturing a diversity of perspectives.Conclusions: Our study is one of the first to characterize the social networks inside and outside of medical school that students utilize to discuss and reflect on early significant clinical experiences. Recent commentary in the literature has suggested reflection is diverse and personal in nature and our study offers empirical evidence to demonstrate this. Our insights emphasize the importance of moving from an instrumental approach to an authentic socially situated approach if we wish to cultivate reflective lifelong learning.